The Video Head Impulse Test and the Oculomotor Test in Patients with Vestibular Migraine - Nedim Turğut; Özge Kale; Adnan Fuat Büyüklü (ENT Updates, 2024)
To compare the results of the Oculomotor Random Saccade test, Positional test and Video Head Impulse Test (vHIT) patients with Vestibular Migraine (VM) and in healthy volunteers and to determine the sensitivity of these tests in revealing peripheral vestibular hypofunction. A retrospective examination was made of the data of 33 patients (mean age:44.72±13.73 years) diagnosed with VM in a tertiary level neuro-otological clinic between June 2020 and December 2022. The oculomotor random saccade test, positional tests, vHIT gain and asymmetry results were compared with those of 33 healthy volunteers and statistically analysed. Gaze nystagmus was observed in 18.18% of VM patients. The positional tests were abnormal in 15.1% of the VM patients. The mean velocity was seen to be increased 18.2% patients in VM. The right-side accuracy values were determined to be <80% in 4 (12.2%) patients in VM. The two groups were similar in terms of vHIT vestibulo-ocular reflex (VOR) gain values. Vestibular deficit of VOR gain <0.7 was determined in 30.3% of the VM patients. VOR gain asymmetry of >20% was observed in 11 (33.3%) VM patients (p>0.05). Abnormalities in the oculomotor saccade test results and differentiated asymmetry values with reduced VOR gain values may be observed in patients with VM. It should be kept in mind that vHIT results may be affected in patients with VM.